DIETARY FOOD FORTIFIED WITH OROTIC ACID AND LIVER FUNCTION - Buang, Yohanes (Makara Journal of Science, 2011)
The effects of dietary food fortified with orotic acid (1.0%) on liver function were studied in rats. The rats fed with orotic acid promoted liver triglyceride content markedly, that was 5-fold higher than that of the control. The liver malondialdehyde (MDA) content increased by 10%, but the gluthation peroxidase (GSH-Px) activity decreased by 50%. The serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities increased by 25% and 30%, respectively. Therefore, the decreased GSH-Px activity was associated with the promotions of AST, ALT, and the liver MDA levels. In conclusion: dietary orotic acid promotes lipid peroxidation but reduces the rate of the antioxidant enzyme. Therefore, dietary food fortified with orotic acid attenuates the liver function.